Awareness, Understanding, and Adoption of Precision Medicine to Deliver Personalized Treatment for Patients With Cancer: A Multinational Survey Comparison of Physicians and Patients. (17th February 2016) - Ciardiello, Fortunato; Adams, Richard; Tabernero, Josep; Seufferlein, Thomas; Taieb, Julien; Moiseyenko, Vladimir; Ma, Brigette; Lopez, Gustavo; Vansteenkiste, Johan F.; Esser, Regina; Tejpar, Sabine
Abstract: Background: Two separate multinational surveys of oncologists and patients with cancer were conducted to assess the awareness and use of biomarkers in clinical practice. These data explore the self-reported and physician-assessed levels of patient cancer literacy and factors affecting physicians' choice to use biomarkers in treatment decisions. Patients and Methods: Interviews were conducted via telephone with patients and online with physicians. Physicians had 3–35 years of experience; were treating more than 15 patients/month; and specialized in breast, lung, or colorectal cancer. Patients had received treatment for breast, lung, or colorectal cancer within the previous 5 years. Results: Interviews with 895 physicians and 811 patients were completed. Most patients and physicians reported that patients understood that a tumor could be tested to determine what treatment would be most effective (78% and 73%, respectively) and that patients would be willing to participate in a personalized treatment plan. Whereas 85% of patients felt that they understood their treatment when it was explained to them, only 23% of doctors felt that their patients were always fully informed. Most physicians (90%) reported using biomarkers; among the 10% not performing biomarker analysis, the most cited obstacles were local availability, speed of obtaining results, and cost. Conclusion: These data demonstrate wide global use of biomarker testing but with regional variations reflecting cultural and local practice. Self-reported and physician-assessed cancer literacy, although generally high, highlighted important regional variations and the need to provide patients with additional information. Abstract : Although there were important regional variations, patients and physicians were generally aware of the advances in precision medicine and showed willingness to participate in associated biomarker testing. However, considerable opportunity remains for physicians and support groups to better educate patients about the ability of biomarker testing to inform the most effective, personalized treatment strategy, tailored to the patient's own tumor.